Penerapan Keadilan Restoratif Dalam Tindak Pidana Penganiayaan (Studi Kasus Pada Polsek Namrole) - Nurlatu, Yohanis Onyong; Wadjo, Hadibah Zachra; Leasa, Elias Zadrach (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Application Restorative Justice is an alternative settlement of criminal cases focused on punishment which is transformed into a process of dialogue and mediation involving perpetrators, victims, families of perpetrators/victims, and other related parties to jointly create an agreement on a fair and balanced settlement of criminal cases for both parties. Victims and perpetrators by prioritizing restoration to their original state and restoring good relations and the community. Purposes of the Research: Review and Analyze the Urgency and Implementation of the Chief of Police Regulation Number 08 of 2021 in Handling Cases of Crime of Persecution at the Namrole PoliceMethods of the Research: The method used in this research is a type of normative research or what is called library research, which is research that examines document studies, namely using various secondary data such as laws and regulations, legal theory, and can be in the form of opinions of scholars.Results of the Research: The application of restorative justice can only be carried out on the crime of light maltreatment as referred to in Article 352 of the Criminal Code paragraph (1). belonging to Article 354 paragraph (1) of the Criminal Code and Article 90 of the Criminal Code must be processed in accordance with applicable legal procedures so that there is no inequality or injustice in the law because the true application of restorative justice refers to restoring the original state, aiming to empower victims, perpetrators, families, to correct an unlawful act by using awareness and responsibility.